PENERAPAN E-GOVERNMENT DALAM MENDUKUNG TRANSPARANSI DAN KETERBUKAAN INFORMASI PUBLIK (STUDI KASUS WEBSITE RESMI PEMERINTAH KOTA MANADO) - Sofany Russo Rumimpunu; Johny R. E. Tampi; Very Y. Londa (AGRI-SOSIOEKONOMI, 2021)
The development of e-government in Manado city is one of the programs implemented by the Manado city government to facilitate services to the public and private parties using advances in information technology. This research aims to explain the implementation of E-government in supporting transparency and openness of public information in Manado City. The research was conducted by descriptive method with qualitative approach, data obtained through observation, interview and secondary data. The focus of this research used Charles Jones's theory of application or application. The results showed that the implementation of e-government in Manado city is still not going well because the Department of Communication and Informatics is still experiencing constraints on its implementation such as lack of employees, little funds, facilities and infrastructure that have not been supported, lack of community participation, lack of commitment from the government so as to have an impact on transparency and openness of public information.